Non-invasive Determination of Myocardial Lipid Content in Fabry Disease by 1H-MR Spectroscopy - Petritsch, B.; Köstler, H.; Machann, W.; Horn, M.; Weng, A. M.; Goltz, J. P.; Hahn, D.; Niemann, M.; Weidemann, F.; Wanner, C.; Beer, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: In Fabry disease (FD), a progressive deposition of sphingolipids is reported in different organs. The present study applied 1H magnetic resonance spectroscopy (MRS) to investigate the myocardial lipid content in FD.Materials and Methods: In patients (PTS, n = 15) with genetically proven FD, 1H MRS of the heart was acquired in the same examination as routine cardiac cine and late enhancement MR imaging. Healthy volunteers (n = 11) without history of cardiac disease served as control (CTL). Myocardial triglycerides in vivo were quantified in 1H MRS. Left ventricular (LV) ejection fraction (EF) and late enhancement were assessed for the determination of LV systolic function, and onset or absence of myocardial fibrosis. Results: All 1H MRS revealed resonances for intramyocardial triglycerides. Clinical parameters, e. g. EF (PTS 64 ± 2 % vs. CTL 61 ± 1 %) were similar in PTS and CTL or showed a non-significant trend (LV mass). Apart from a single patient with elevated myocardial triglycerides, no significant impact of Fabry disease on the triglyceride/water resonance ratio (PTS 0.47 ± 0.11 vs. CTL 0.52 ± 0.11 %) was observed in our patient cohort. Conclusion: A comprehensive cardiac evaluation of morphology, function as well as metabolism in Fabry PTS with suspected cardiac involvement is feasible in a single examination. No significant effect of myocardial triglyceride deposition could be observed in patients. The remarkably high myocardial triglyceride content in one patient with advanced FD warrants further studies in PTS with an extended history of the disease.
Keywords: cardiac; MR-imaging; MR-spectroscopy; genetic defects; molecular imaging